2022
DOI: 10.5935/1518-0557.20210040
|View full text |Cite
|
Sign up to set email alerts
|

Adding Weekly Intramuscular Progesterone to a Twice Daily Vaginal Progesterone Capsule for Luteal Phase Support in IVF/ICSI Cycles Results in Similar Live Birth Rates

Abstract: Objective To compare pregnancy outcomes in patients undergoing artificial reproductive treatment (ART) and fresh embryo transfer (ET) who received twice-daily vaginal progesterone capsule (Cyclogest) alone verses twice daily vaginal progesterone capsule (Cyclogest) plus weekly intramuscular Hydroxyprogesterone Capronate (Proluton depot) for luteal phase support. Methods A retrospective cohort study that included 1162 patients who completed fresh ART/ET cycle from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Likewise, two recently published retrospective studies compared combined IM and vaginal progesterone vs. either IM or vaginal progesterone only LPS. Both studies showed similar outcomes for all study arms (7,8). Similarly, no significant differences were found between low-dose vs. high dose vaginal agents, short vs. long protocol, micronized vs. synthetic formulation or other administration forms (vaginal ring, gel) (3).…”
Section: Progesterone Routes Of Administration In Fresh Embryo Transfersmentioning
confidence: 92%
“…Likewise, two recently published retrospective studies compared combined IM and vaginal progesterone vs. either IM or vaginal progesterone only LPS. Both studies showed similar outcomes for all study arms (7,8). Similarly, no significant differences were found between low-dose vs. high dose vaginal agents, short vs. long protocol, micronized vs. synthetic formulation or other administration forms (vaginal ring, gel) (3).…”
Section: Progesterone Routes Of Administration In Fresh Embryo Transfersmentioning
confidence: 92%
“…Some authors have also experimented the administration of two routes of progesterone; weekly intramuscular progesterone in addition to a classic luteal phase supported by vaginal progesterone versus vaginal progesterone alone with similar results between the two treatments after fresh embryo transfer (21).…”
Section: Introductionmentioning
confidence: 99%